2017
DOI: 10.1021/acsnano.7b03494
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Cell–Material Interface with Nanometer Resolution by Focused Ion Beam/Scanning Electron Microscopy

Abstract: The interface between cells and non-biological surfaces regulates cell attachment, chronic tissue responses, and ultimately the success of medical implants or biosensors. Clinical and laboratory studies show that topological features of the surface profoundly influences cellular responses, e.g. titanium surfaces with nano- and microtopographical structures enhance osteoblast attachment and host-implant integration as compare to smooth surface. To understand how cells and tissues respond to different topographi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
177
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 160 publications
(192 citation statements)
references
References 44 publications
13
177
0
Order By: Relevance
“…Bianxiao Cui’s and Yi Cui’s Laboratories have demonstrated that nanopillar arrays can minimally invasively pin embryonic cortical neuronal cell bodies 39 and, more recently, that plasma membranes of HL-1 cardiomyocytes cultured on a quartz substrate with nanopillars can deform to wrap around the pillars but will not readily deform outwardly around invaginating structures (Figure 2C,D). 40 This differential membrane response to varying nanoscale topographical features must be considered during design of materials to be implanted into biological systems, as the tightness of the interface can vary significantly. At the membrane protein level, it was found that positively curved membranes are clathrin-mediated endocytosis (CME) hot spots.…”
Section: Achieving Robust Biointerfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bianxiao Cui’s and Yi Cui’s Laboratories have demonstrated that nanopillar arrays can minimally invasively pin embryonic cortical neuronal cell bodies 39 and, more recently, that plasma membranes of HL-1 cardiomyocytes cultured on a quartz substrate with nanopillars can deform to wrap around the pillars but will not readily deform outwardly around invaginating structures (Figure 2C,D). 40 This differential membrane response to varying nanoscale topographical features must be considered during design of materials to be implanted into biological systems, as the tightness of the interface can vary significantly. At the membrane protein level, it was found that positively curved membranes are clathrin-mediated endocytosis (CME) hot spots.…”
Section: Achieving Robust Biointerfacesmentioning
confidence: 99%
“…(C,D) Surface topography affects cleft distance between cell membrane and material surface. Adapted with permission from ref 40. Copyright 2017 American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…The cross-section was performed as presented in ref. [21] using a focused ion beam (FIB) prepared sample (see Experimental Section). The image demonstrates the coverage of PEDOT:PSS on gold, the encapsulation of parylene around it and most importantly, the tight attachment of the cell on the microelectrode.…”
Section: Mea Design and Growth Of Cortical Cellsmentioning
confidence: 99%
“…For the cross-sectional images, the cells were further processed with a ROTO staining, uranyl acetate, dehydrated, and embedded as presented in ref. [21]. Cross-sections were made and polished, fixing a voltage at 30 kV and current at 80 pA. A more detailed description of the FIB-SEM procedure is given in ref.…”
Section: Mea Preparation For Cell Culture: Protein Coatingmentioning
confidence: 99%
See 1 more Smart Citation